Case Report: Bilateral syringocele in an adolescent—area of focus - Osipov, I. B.; Lebedev, D. A.; Uzintseva, A. A.; Sidorova, N. A. (Frontiers in Pediatrics, 2023)
Rationale: Cystic dilatation of the bulbourethral gland duct (Cowper's syringocele) (CS) is a rare urethral pathology. No more than 150 cases of CS have been described in the literature, of which the vast majority in children and with an unilateral location. Bilateral CS were mentioned in 8 cases, however detailed anatomy and clinical courses are not reported. We report on a case of bilateral CS with cavity junctions through the medial septum and it´s successful minimally invasive treatment in an adolescent.Case presentation: A 16-year-old adolescent patient complaints of painful urination and the presence of post-micturition urinary dribbling. MRI, urethrography and ureteroscopy data allowed to establish the diagnosis and form of CS. Surgical treatment performed: endoscopic marsupialization of both CS chambers. At follow-up examination after 7 months, the complaints had ceased, there was complete normalisation of urination. The maximum flow rate during uroflowmetry was 35 ml per second, on voiding cystourethrography the residual cavities were not contrasted, there was no residual urine or bacteriuria.MRI and retrograde urethrography made it possible to visualize changes in the bulbous part of the urethra, ureteroscopy was the leading imaging modality. The complex of these studies was applied precisely because of the suspicion of the presence of a cavity communicating with the urethra. Minimally invasive surgical treatment for double-chamber CS was successful and had no complications.